„O Niepodległą i Chrystusową Polskę” – „Orlęta” rudnickie (1947-1949) - Wieliczka-Szarkowa, Joanna (Fides, Ratio et Patria. Studia Toruńskie, 2018)
Established in 1947 in Rudnik nad Sanem, “Orlęta” was the largest, after the war, illegal organization in the former province of Rzeszów. It was created by several students of the State Junior High School and High School in Rudnik nad Sanem: Stanisław Mandecki, Lesław Popowicz, Władysław Konefał and Kazimierz Dechnik. In the organization, the rules of the Roman Catholic religion were in force, which served the idea of the Polish Christ and were expressed in the slogan borrowed from the scouting of the pre-war Homeland - Science - Virtue. The organization developed quickly and soon it had more than 100 members from the age of 16 to 25. The “Orlęta” departments were also established in Nisko, Stalowa Wola, Łańcut, Rzeszów, Brzozów and Biłgoraj. There was a strict conspiracy. “Orlęta” focused on self-education and awareness. All the time, the boys took part in the campaign of picking up communist posters, posters, banners and red flags, as well as displaying and distributing patriotic leaflets and proclamations. They also published two underground newspapers. The Orlęta also carried out several military actions aimed at gaining funds for the organization’s activities. Liquidation of the “Orlęta” began in 1949. Its members, after a series of trials, spent several years in prisons. The leader of the group Stanisław Mandecki was sentenced to 15 years in prison, of whom he served seven years and three months.